The measure of merit : talents, intelligence, and inequality in the French and American republics, 1750-1940 (Princeton University Press, 2007)
"In this wide-ranging account of American and French understandings of merit, talent, and intelligence over the past two centuries, John Carson tells the story of how two nations wrestled scientifically with human inequalities and their social and political implications. Surveying a broad array of political tracts, philosophical treatises, scientific works, and journalistic writings, Carson chronicles the gradual embrace of the IQ version of intelligence in the United States, while in France, the birthplace of the modern intelligence test, expert judgment was consistently prized above such quantitative measures.